Menemukan Tenang di Tengah Tekanan: Self-Compassion, Gratitude sebagai Pereda Stres Akademik pada Mahasiswa - Amanda Zahra, Carissa; Dwi Yuwono Puji Sugiharto (Program Studi Bimbingan dan Konseling, Universitas Negeri Jakarta, 2025)
Students frequently face persistent academic pressure, which impacts their psychological well-being and academic performance. To address this challenge, various strength-based psychological approaches have been explored, including the enhancement of self-compassion and gratitude. This study aims to conduct a systematic literature review to identify and analyze the contributions of self-compassion and gratitude in reducing academic stress among students. The method employed is a Systematic Literature Review (SLR) guided by PRISMA. Articles were sourced from Google Scholar, PubMed, and Publish or Perish (2015–2024), with inclusion criteria focusing on peer-reviewed journals discussing at least one of the two key variables in the student context. From the search and selection process, 12 articles were analyzed. Findings indicate that self-compassion reduces self-criticism and enhances emotional regulation, while gratitude strengthens psychological resilience and fosters positive perceptions of academic pressure. The study recommends integrating both approaches into strength-based counseling services as a preventive and promotive strategy for managing academic stress.